Can Kinesiotaping Reduce Pain in Rib Fractures?: A Randomized Prospective Study - Dal İ; Bektaş Ö; Kader S; Bodur G (Journal of Pain Research)
İsmail Dal,1 Özgür Bektaş,2 Sibel Kader,3 Gözde Bodur3 1Department of Thoracic Surgery, Kastamonu University, Kastamonu, Turkey; 2Department of Physical Therapy and Rehabilitation, Kastamonu University, Kastamonu, Turkey; 3Department of Thoracic Surgery, Kastamonu Training and Research Hospital, Kastamonu, TurkeyCorrespondence: İsmail Dal, Department of Thoracic Surgery, Kastamonu University, Kuzeykent, Ergenekon St. Nu: 9G1-1, City Center, Kastamonu, Turkey, Tel +905446533224, Email drismaildal@gmail.comIntroduction: The aim of this study is to investigate the effect of kinesiotaping on pain scores in patients with rib fractures following isolated thoracic trauma.Materials and Methods: In this randomized prospective study, patients with isolated thoracic trauma and rib fractures were randomized into kinesiotaping and control groups between January 24, 2024, and October 1, 2024. Patients in the control group received standard analgesic treatment. In the kinesiotaping group, kinesiotaping bands were applied in addition to the standard treatment. Pain scores using the visual analog scale (VAS) were recorded at admission, the 24th hour, the 4th day, and the 7th day, and the results were statistically compared.Results: A total of 118 patients were evaluated. Eighty-four patients did not meet the inclusion criteria. The 34 patients included in the study were randomized into kinesiotaping and control groups. The two groups were demographically homogeneous. On the 4th day, the mean VAS score was significantly lower in the kinesiotaping group (2.7 ± 1.2) compared to the control group (4.1 ± 1.9) (p = 0.037). No statistically significant difference in VAS scores was observed on the other days.Conclusion: In patients with rib fractures, pain scores decreased more rapidly in those treated with analgesics plus kinesiotaping compared to those treated with analgesics alone.Trial Registration: ClinicalTrials.gov, NCT06222320. Registered on January 15, 2024.Keywords: rib fracture, pain, visual analog scale, kinesiotaping